(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics and identify causes of postmenopausal bleeding in women at the National Hospital of Obstetrics and Gynecology. Materials and Methods: A prospective cross-sectional descriptive study was conducted on 165 postmenopausal women presenting with vaginal bleeding at the National Hospital of Obstetrics and Gynecology from February 2025 to July 2025. Results: The mean age was 62.4 ± 8.65 years. Most patients presented with light or spotting bleeding (83.0%), 64.8% were asymptomatic. On ultrasound, the mean endometrial thickness was 8.72 ± 6.34 mm; with hyperechoic intrauterine masses being the most common finding (18.2%). Histopathology from endometrial aspiration revealed benign lesions in 71.85% of cases. Benign etiologies accounted for 74.6%, with genital atrophy being the most frequent (27.9%), endometrial cancer was detected in 23%. Factors associated with malignant etiology included recurrent bleeding, purulent discharge, endometrial thickness >10 mm, loss of the endometrial–myometrial junction, and hyperechoic intrauterine mass (p < 0.05). Conclusion: Postmenopausal bleeding is primarily caused by benign conditions; however, the prevalence of endometrial cancer remains high. Combining clinical examination with ultrasound and histopathology plays a crucial role in the diagnosis and management orientation of these patients.